PREVALENCE OF MYCOBACTERIUM TUBERCULOSIS AMONG CHILDREN AT THE RESERVOIRS OF INFECTION IN THE REPUBLIC OF TAJIKISTAN - O.I. BOBOKHOJAEV; U.YU. SIRODJIDINOVA; S.M. SAYDALIEV; R.S. BOZOROVA (Avicenna Tajik State Medical University, 2021)
Objective: To study the prevalence of Mycobacterium tuberculosis at the infection reservoirs in the Republic of Tajikistan among children and the impact of BCG vaccination assessed by tuberculin skin test. Methods: The results of tuberculin skin test in children from Mycobacterium tuberculosis seedbeds in the Republic of Tajikistan were analyzed in the city of Bokhtar (n=176) and the village of Dusti, Khatlon region (n=124). The impact of BCG vaccination in children under 6 years of age was considered in interpretation of the tuberculin skin test results. Results: The positive result of the tuberculin skin test in children aged 0-6 years was found in 64.7% of cases, 7-14 years - in 47.0% and 15-17 years - in 61.5% respectively. It was shown that rate of high degree of tuberculin sensitivity in children from Mycobacterium tuberculosis reservoirs increased with age. The highest rate of tuberculin sensitivity was observed in 15-17 years old children, and among them in the city - 22.2%, in the village - 27.3%; followed by the age group 7-14 years: in the city - 20%, in the village - 25%. In the age group 0-6 years, this indicator was 2.4% and 3% respectively. Conclusion: The analysis shows that the situation with tuberculosis in the reservoirs of infection, especially in children aged 7 years and over, is challenging. For the correct interpretation of tuberculin test results in children under 6 years of age, it is important to consider the effect of BCG vaccination. Prevalence of the tuberculosis among the children at the infection reservoirs is high, which requires special attention and measures for comprehensive prevention of tuberculosis in its seedbeds. Insufficient monitoring of contact children residing in the reservoirs of infection is an important factor contributing to the late detection of severe and complicated forms of tuberculosis in children.